EFFECT OF TEMPORARY CEMENTS ON THE BOND STRENGTH OF A RESIN CEMENT TO A PRE-HYBRIDIZED DENTIN - Lima, Marcio Ferreira; Maciel, Carolina Menezes; Oliveira Correia, Ayla Macyelle de [UNESP]; Griza, Sandro; Melo de Mendonca, Adriano Augusto (Univ Federal Uberlandia, 2017)
This study assessed the bond strength of a resin cement when Immediate Sealed Dentin (ISD) was contaminated by different temporary cements applying a microshear test. Forty-eight fragments of third molar crowns were mounted in acrylic resin and worn until the dentin was exposed. The substrates were sealed with a 3-step conventional adhesive system and divided into four groups (n= 12): Control (without temporary cement) and three groups that used different temporary cements - Provy, RelyX Temp NE, and Provitemp. The temporary cements were removed after 7 days of storage. Resin cement RelyX ARC was applied to the contaminated substrates. Microshear bond strength was evaluated using a universal testing machine (0.5 mm/min). Data was analyzed with ANOVA and a Dunnett post-hoc test (p < 0.05). Additionally, three samples from each group were prepared for scanning electron microscope analysis. Means and standard deviations of microshear bond strength (MPa) were 17.96 +/- 1.65, 16.70 +/- 1.43, 20.43 +/- 1.30 and 33.75 +/- 4.72 for Control, Provy, RelyX Temp, and Provitemp, respectively. Statistically significant difference was observed between the Control and Provitemp samples (p=0.0002). Adhesive failures were dominant (50%), followed by cohesive failures with cement (26%), and cohesive failures with dentin (24%). Residues of Provy and Provitemp were observed on the sealed dentin. Provitemp temporary cement sealing increased the microshear bond strength of the resin cement on dentin treated with IDS.
Keywords: Dental materials; Resin cements; Bond strength; Immediate dentin sealing